THE DEVELOPMENT OF CAPACITY BUILDING TO IMPROVE THE QUALITY OF HUMAN RESOURCES AMONG SMALL AND MEDIUM ENTERPRISES - Dheasy Amboningtyas; Yulianeu Yulianeu (Manajemen Bisnis, 2019)
Small and medium enterprises (SME) are those of business groups which are believed to survive even when economic crisis occurs. The increasing number of those business groups allows more job opportunities for people, and thus it could impact positively towards the decreasing number of unemployments. Unfortunately, the level of managerial skills and ability among SME are relatively low due to a number of SME entrepreneurs who still hold Bachelor degrees. In addition, the fact indicates that the quality of SME resources is low, especially in the fields of management, organization, mastery of technology and marketing. The low educational level among small and medium entrepreneurs was apparently not supported by capacity building through training, education, and programmed comparative studies. On the other hand, human resources (HR) also plays an important role in gaining success, because sophisticated and complete facilities cannot guarantee the success of an organization if they are not supported by quality of human resources who will use the facility. This study aims at examining strategies that can be used by SME as an effort to improve HR capacity using purposive sampling method; and then the data is analyzed using multi-linear regression. The result shows that capacity development which is proxied through education, skills and ability variables partially or simultaneously have positive and significant effects on HR development.